Autoethnography Towards Community Accountability: Queerlandia, Belonging, and Hope - Been, Sophie Johanna (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2025)
In this work, I intertwine my own reflections on community with two recent queer Canadian autobiographical works: Kai Cheng Thom’s I Hope We Choose Love: A Trans Girl’s Notes from the End of the World (2019) and Mx. Sly’s Transland: Consent, Kink, & Pleasure (2023). I explore challenges to community accountability within queer spaces and position autoethnography as a site for community intervention. I ask how we identify and address harm within our communities when the very existence of these spaces seems precarious. Subsequently, I illustrate how the intersections of desire, harm, and accountability have been narrativized in our community spaces, and how the stories we tell and respond to actively shape the conversation that is community.